Analisis Pengaruh Service Failure terhadap Kepuasan Pelanggan Melalui Service Recovery pada Pelanggan OYO di Kota Medan - Muhammad Hajar Haitami; Syafrizal Helmi Situmorang (INOBIS: Jurnal Inovasi Bisnis dan Manajemen Indonesia, 2019)
The purpose of this study was to determine the influence of service failure on customer satisfaction through service recovery for OYO customers in Medan City. This type of research is associative research. The population in this study were customers of OYO in Medan City. The sample in this study were 150 customers of OYO in Medan City who have complained. The analytical method used in this study is descriptive analysis method and path analysis that was proceseed statistically with SPSS for windows software. The result of the mediation test show that service recovery significantly mediates the relationship between service failure and customer satisfaction. The result of path analysis, the service failure variable has a negative and significant influence on customer satisfaction, the service failure variable has a negative and significant influence on service recovery, and the service recovery variable has a positive and significant influence on customer satisfaction. Based on the size of the Adjusted R-square, it can be seen that the service failure and service recovery variables simultaneously influence the customer satisfaction of 49,5% while the remaining 50,5% is influenced by other factors outside the variables studied.